Hypolipidemic action of oral applications of edible fats - Levitsky, A. P.; Dvulit, I. P.; Khodakov, I. V. (Journal of Education, Health and Sport, 2018)
Background. To determine the effect of oral fatty applications on the content of triglycerides in the serum and liver of rats.Methods. As edible fats, ordinary sunflower oil, high-oleic sunflower oil “Olivka” and butter, as well as the same oils after heat treatment, were used. Application of oils (0.5 g) on the oral mucosa was carried out once a day for 3 days. After euthanasia on the 4th day, the content of triglycerides (TG) in the serum and in the liver was determined. The content of malondialdehyde (MDA) was also determined in the liver. The ratio of the level of TG in serum and in the liver was calculated fat-incretory function of the liver.Results. Oral fatty applications cause a decrease in serum TG and increase them in the liver. In the liver, the content of MDA and the fat-incretory function decreases. Conclusion. Oral fatty applications cause hypotriglyceridemia, reduce the level of peroxidation in the liver and cause hepatosteatosis.